Synthesis and activity of newly designed aroxyalkyl or aroxyethoxyethyl derivatives of piperazine on the cardiovascular and the central nervous systems. Issue 21 (1st November 2016) - Waszkielewicz, Anna Maria; Kubacka, Monika; Pańczyk, Katarzyna; Mogilski, Szczepan; Siwek, Agata; Głuch-Lutwin, Monika; Gryboś, Anna; Filipek, Barbara
Graphical abstract: New phenylpiperazine derivatives were synthesized and evaluated for binding to adrenergic receptors, α1 -adrenolytic properties in vitro and hypotensive activity in vivo. 1-[4-(2, 6-dimethylphenoxy)butyl]-4-(2-methoxyphenyl)piperazine hydrochloride possessed the most beneficial pharmacological profile. Structure–activity relationship for the tested compounds was discussed. Abstract: In the search for new hypotensive agents some new aroxyalkyl or aroxyethoxyethyl derivatives of piperazine have been synthesized and evaluated for their pharmacological properties. Pharmacological tests included receptor binding assays toward adrenergic receptors α1, α2 and β1, additionally 5-HT1A, functional bioassay and in vivo evaluation of hypotensive activity as well as antidepressant-like potential. All the tested compounds exhibited α1 -antagonistic properties, three of them possessed also hypotensive activity in rats. The most promising compound3 1-[4-(2, 6-dimethylphenoxy)butyl]-4-(2-methoxyphenyl)piperazine hydrochloride was a selective α1 receptor antagonist ( K i  = 23.5 ± 1.3, α1 /α2  = 15.77, p K B  = 8.538 ± 0.109). It was active in all tested doses in vivo (1, 0.5, and 0.1 mg/kg) and it reduced blood pressure by 10–13% at the dose of 1 mg/kg (rats, i.v.). Compound5 1-[2-(2, 3-dimethylphenoxy)ethoxyethyl]-4-(2-methoxyphenyl)piperazine dihydrochloride exhibited the lowest dose for antidepressant-like activity 5 mg/kg b.w. (mice, i.p.) without influence on spontaneous activity (mice, i.p.).